Lọc và nhận dạng thích nghi trong bài toán điều khiển hệ ngẫu nhiên - Lân, Vũ Như; Hưng, Vũ Chấn; Sơn, Hoàng Hồng (Journal of Computer Science and Cybernetics, 2016)
A new adaptive approach based on the principle of separating the discrete measuring functional is suggested.